Peripheral blood hemophagocytosis in an unusual lymphoma. Issue 1 (2nd December 2014) - Fragasso, Alberto; Mannarella, Clara; Ciancio, Angela; Scarciolla, Oronzo
<x xml:space="preserve">Abstract</x> We describe a patient with fever, pancytopenia, and hepato‐splenomegaly associated with the finding of neoplastic lymphoid cells and histiocytes with hemophagocytosis in the peripheral smear; the diagnostic features were suggestive of a biological overlap between a large B‐cell lymphoma with intravascular involvement and the Asian variant of intravascular B‐cell lymphoma. <boxed-text content-type="graphic" id="ccr3124-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>